2019
DOI: 10.1016/j.ebiom.2019.01.054
|View full text |Cite
|
Sign up to set email alerts
|

SA-49, a novel aloperine derivative, induces MITF-dependent lysosomal degradation of PD-L1

Abstract: BackgroundProgrammed death-ligand 1 (PD-L1) is a T-cell inhibitory checkpoint molecule that suppresses antitumor immunity. Anti-PD-L1 antibodies have shown remarkable promise in treating tumors, but the patient response rate is low. Therefore, small-molecule checkpoint inhibitors blocking PD-L1 function are urgently needed.MethodsChanges of protein expression and phosphorylation levels were determined by immunoblotting. The level of Membrane PD-L1 was examined by flow cytometer. Cytotoxicity of T cells and NK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 48 publications
0
57
0
Order By: Relevance
“…Aloperine, a natural alkaloid isolated from the herb S. alopecuroides , has been reported to exhibit anticancer activity in various human cancers [1,7,12,15,18,20]. Previous studies have demonstrated that aloperine mediates cell proliferation, cell cycle inhibition and regulation, apoptosis induction, and tumor migration/invasion and suppression [1,7,12,15,18,19,26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aloperine, a natural alkaloid isolated from the herb S. alopecuroides , has been reported to exhibit anticancer activity in various human cancers [1,7,12,15,18,20]. Previous studies have demonstrated that aloperine mediates cell proliferation, cell cycle inhibition and regulation, apoptosis induction, and tumor migration/invasion and suppression [1,7,12,15,18,19,26].…”
Section: Discussionmentioning
confidence: 99%
“…Aloperine, a quinolizidine alkaloid isolated from Sophora alopecuroides , reportedly exhibits multiple pharmacological activities, including anti-inflammatory, antiallergenic, antiviral, antimicrobial, antinociceptive, and antitumor effects; moreover, it exhibits protective effects against renal and neuronal injuries as well as pulmonary fibrosis [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20]. Aloperine exerts antitumor effects against multiple human cancers, including multiple myeloma; colon, breast, prostate, and thyroid cancers; and osteosarcoma [1,7,12,15,18,20]. In previous studies, our and other research groups have demonstrated that aloperine can suppress tumorigenesis, inhibit tumor cell proliferation, and induce cell cycle arrest and apoptosis in various human cancer cells [1,7,12,15,18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the application of aloperine, the injury of pulmonary vascular endothelial cells gets significantly improved, the shape of the nucleus of endothelial cells becomes basically normal, and the expansion of the Golgi body and endoplasmic reticulum gets improved. It suggests that rotenone can improve pulmonary hypertension induced by monocrotaline through the NF-κB p65 signaling pathway [50].…”
Section: Piperidine Alkaloidsmentioning
confidence: 99%
“…Heretofore, ALO has been reported to exert therapeutic effects against pulmonary hypertension, renal injury and colon cancer (Zimecki, 1987). ALO derivatives with a unique endocyclic scaffold have also been designed, synthesized and evaluated as HCV, PD-L1 and HIV-1 entry inhibitors (Dang et al, 2016; Zhang et al, 2019). Moreover, analysis demonstrated that ALO suppresses tumorigenesis, suggesting its potential therapeutic use in human cancers and multidrug-resistant cancers.…”
Section: Introductionmentioning
confidence: 99%